The role of FGF23 in cardiovascular disease: From pathophysiology to biomarker and therapeutic implications - Kurniawan, Ary; Rohman, Mohammad Saifur (Universitas Brawijaya, 2026)
Cardiovascular disease (CVD) remains a leading global cause of mortality, necessitating deeper insights into non-traditional risk factors. Fibroblast growth factor 23 (FGF23), a hormone central to phosphate and vitamin D regulation, has emerged as a pivotal contributor to CVD pathogenesis. This review synthesizes evidence linking elevated FGF23 levels to adverse cardiovascular outcomes, including left ventricular hypertrophy, vascular calcification, hypertension, and atrial fibrillation in both chronic kidney disease (CKD) and individuals with preserved renal function. Mechanistically, FGF23 exerts direct effects on cardiac remodeling and calcium handling while indirectly promoting CVD via dysregulated mineral metabolism, renin-angiotensin-aldosterone system (RAAS) activation, and inflammatory pathways. Paradoxically, its compensatory rise in CKD to counteract hyperphosphatemia becomes maladaptive, accelerating cardiovascular pathology. Despite its potential as a biomarker, challenges persist in establishing causality, disentangling confounding factors (e.g., inflammation, renal function), and developing targeted therapies that mitigate pathological effects without disrupting physiological phosphate homeostasis. Future research must prioritize defining context-specific FGF23 thresholds, elucidating cardiac versus systemic signaling mechanisms, and advancing receptor-specific interventions. Bridging these gaps will require multidisciplinary collaboration to translate FGF23’s dual roles, as both a compensatory hormone and a disease mediator into clinical strategies for CVD risk stratification and management.